A Systematic Literature Review of Digital Marketing Communication: A Review of Extant Research and Future Directions - Mira Maulani Utami (Nusantara Science and Technology Proceedings, 2023)
Digital marketing communication, communication through digital or electronic media among businesses or electronic media among businesses and consumers, is quickly rapidly. The purpose of this study is to conduct a comprehensive analysis of existing study trends in digital marketing communication research. Based on a review of numerous international scientific journals. The study used Publish or Perish with Scopus (Q1-Q4) as a database and conducted a thorough examination. Bibliometric technique using Vosviewer is being implemented on this research. Then, to categorize and discuss prospective future research, an input-process-output framework was applied. A Total of 111 articles published in journals from 2013 to 2023 were selected. This study highlights the evolving volume of studies, and keywords. This study provides future directions for research on digital marketing communication. This study reveals 5 findings, first, digital marketing communication research is integrated with digital marketing communication and competitive advantage, second digital marketing communication in the context of tourism should be improved, third research on digital marketing communication in developed countries is more advanced than in developing countries, fifth, most of the research is in the context of Business to Consumer, on the other hand, that the context of Business to Business is very necessary to be analyzed . Based on literature synthesis, the study provides insights into practical managerial implications and provides the groundwork for future studies. This study will help researchers understand the role and influence of digital marketing. These approaches can offer the insights that managers need to better formulate digital.